Mendeteksi Arus Kas Operasi Overstated pada PT Weha Transportasi Indonesia - Kusfebriana, Riszka Amalia; Sutriani, Windi; Pratama, Mhd Aprialdi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
Operating cash flow inflation is often used by companies as a strategy to create a healthier financial image in the eyes of investors and other stakeholders. The purpose of this study is to detect and analyze the possibility of cash flow inflation at PT. Weha Transportation Indonesia. This research is descriptive qualitative. Data were collected from published financial statements from 2023-2024 from the company's official website at https://whitehorsegroup.co.id/. The data were then reviewed using a checklist of warning signs and analysis techniques for detecting overstated operating cash flows, namely by answering questions from the checklist of warning signs. The results of this study indicate that at PT. Weha Transportation Indonesia Tbk, only 1 out of 6 questions was detected, so it can be said that the company is still in a healthy state, no overstated operating cash flow or operating cash flow inflation was detected.